ORGANIZATIONAL CULTURE AS A PREDICTOR OF EMPLOYEE ENGAGEMENT IN NATIONAL POLICE INSTITUTIONS - Syafruddin Syafruddin; Ekawaty Kristianingsih (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Organizational culture is a central determinant of employee attitudes and behaviours across public sector institutions, particularly in national police organizations where work demands, discretion, and public scrutiny are high. This literature-review study synthesizes empirical and conceptual work from the last ten years (2015–2025) to examine how dimensions of organizational culture predict employee engagement among police personnel. Using a purposive review of peer-reviewed studies, institutional reports, and applied research, the review identifies key cultural dimensions supportive leadership, ethical climate, learning orientation, bureaucratic versus developmental norms, and perceived procedural fairness that consistently relate to engagement outcomes such as vigor, dedication, and absorption. Mechanisms connecting culture to engagement include perceived organizational support, meaningfulness of work, role clarity, and supervisory feedback systems. Evidence indicates that police organizations with stronger developmental cultures and transparent ethical norms show higher employee engagement, greater organizational citizenship behaviour, and lower turnover intentions (Restya, 2024; Rismanto, 2025). Conversely, rigid bureaucratic cultures and perceived unfairness undermine engagement and may reduce discretionary cooperation with reform initiatives (Maphosa et al., 2021). The review highlights implementation contingencies: leadership commitment, resourcing for training, and alignment with career pathways strengthen culture engagement effects. Practical recommendations include diagnosing cultural dimensions with mixed instruments, promoting servant and transformational leadership practices, embedding learning systems, and strengthening procedural justice in decision-making. The paper closes with a prioritized research agenda calling for longitudinal and comparative mixed-methods studies linking cultural change to measurable engagement outcomes and service delivery indicators in policing contexts. Keywords: organizational culture, employee engagement, police institutions, procedural justice